Could Mozambique become a hydrogen hub? - Hanlon, Joseph (Mozambique News Reports & Clippings, 2021)
The proposal for the Mphanda Nkuwa dam 60 km downstream from Cahora Bassa, and using the same water to generate more electricity, is back on the table. The dam has been proposed since the colonial era, but there has never been a market for the electricity. Producing hydrogen would be the perfect market. In this special issue, we look at Mphanda Kkuwa and the potential for hydrogen.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; GP - Tete; L - english / inglês; infrastructure - energy / infrastrutura - energia; natural resources / recursos naturais

What actually is social accountability? - Aston, Thomas (Medium, 2021)
Figuring out “what is the work?” we actually do sounds like a simple task, but in fact, it’s surprisingly difficult.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; G - Rest of the World / Resto do Mundo; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização

Bispo de Pemba critica Nyusi: "Se eu fosse presidente, a minha presença seria outra. Estaria a falar de Cabo Delgado todos os dias" - Castro, Pedro Jorge (Moçambique para todos, 2021)
"Como é que um corrupto pode lutar contra si mesmo? É preciso uma espécie de revolução." As ameaças do governo. A guerra. E o deslocado que disparou contra insurgentes. Entrevista ao Bispo de Pemba.
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - Pemba; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Vale moves to exit coal business - Argus Media (2021)
In its first step to exit the coal business, Brazilian mining firm Vale will acquire all stakes held by Japanese trading house Mitsui in the Moatize coal mine and Nacala corridor coal infrastructure in Mozambique.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

An overview of foreign security involvement in Mozambique (defenceWeb, 2021)
A number of private security companies, foreign governments and militaries have become involved in Mozambique in its fight against the insurgency in Cabo Delgado, but the Mozambican government has so far largely limited external involvement. Nevertheless, there are a number of companies and countries providing security and security assistance to Mozambique. Private military contractors Russian […]
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict / conflito

Hundreds Missing After Mozambique Attack (Human Rights Watch, 2021)
Hundreds of people remain missing five days after an Islamic State (ISIS)-linked armed group known as Al-Shabab raided the town of Palma in Mozambique’s northern Cabo Delgado province, killing and wounding an unknown number of civilians and causing thousands to flee.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Palma; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; security / segurança

Accountability Ecosystems: The Evolution of a Keyword - Halloran, Brendan (Accountability Research Center, 2021)
Efforts to strengthen the accountability of the governing to the governed go back millennia. However, in the past decade there has been a renewed debate about how to advance public accountability. One domain where this conversation has taken place is that of efforts funded by donors (government development agencies and private philanthropies), primarily in the Global South and implemented by a set of national and international actors, including NGOs, private sector project implementors, and international institutions. Unfortunately, much donor-funded work has been underpinned by an understanding of accountability grounded in optimistic assumptions, particularly around the role of transparency and information technology. Early efforts by Rosie McGee and John Gaventa to take stock of this work highlighted the lack of theories of change grounded in a more nuanced, holistic and politically-informed understanding of accountability. Others began questioning the dominant ‘transparency + participation = accountability’ formulation that underpinned many projects; and most of them were just that, projects: start date, end date, work plan, logical framework, funding proposal, budget, etc. It was at the beginning of this discussion about what it takes to achieve real accountability that the term ‘Accountability Ecosystem’ started being used by a few individuals and organizations. The organization I worked for at the time, the Transparency and Accountability Initiative (TAI), had picked up the term, potentially from the organization I work for now, the International Budget Partnership (IBP).[i] I saw the term as a way to advance a more holistic and dynamic way to talk about the interaction of accountability actors, mechanisms and efforts in a given context, and a deliberate step away from more simplistic, linear formulations.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização

Mozambique: Firing in Palma near Total's LNG project, population fleeing - Lusa (Mozambique, 2021)
The town of Palma, in Cabo Delgado, was under gunfire on Wednesday afternoon and the population is fleeing, different sources who were in communication with the headquarters of the district that hosts the gas projects in northern Mozambique told Lusa. Machine gunfire was heard in the town and the
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; extractive industries / indústrias extractivas; private sector / setor privado

Social protection during conflict: reflections on Tigray - Sabates-Wheeler, Rachel; Lind, Jeremy (Institute of Development Studies, 2021)
Conflict and an ensuing humanitarian crisis in Ethiopia’s northern Tigray region have led to substantial population displacement and threaten the lives and livelihoods of millions. In a situation where rising needs outstripped preliminary humanitarian responses and where safety net programmes that were purposed for shock-response have been curtailed or stopped functioning altogether, what are the […]
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; G - Rest of the World / Resto do Mundo; L - english / inglês; Social Protection PEA; conflict / conflito; social protection / proteção social

US hits IS groups in Mozambique, Congo with terror sanctions (AP NEWS, 2021)
WASHINGTON (AP) — The Biden administration on Wednesday designated two Islamic State affiliates in Mozambique and the Democratic Republic of Congo as “foreign terrorist organizations,” imposing...
Section: World News
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Conflict is the new ‘hazard’ on the social protection block - Sabates-Wheeler, Rachel; Slater, Rachel; Lind, Jeremy; Harvey, Paul; Oosterhoff, Pauline; Faith, Becky; Naess, Lars Otto; Selby, Jan; Roberts, Tony; Longhurst, Daniel; Rohwerder, Brigitte; Collyer, Michael; et al. (Institute of Development Studies, 2021)
Although social protection has the potential to address crises in different ways, the evidence base is thematically and geographically patchy. The Foreign, Commonwealth and Development Office-funded (FCDO)-funded Better Assistance in Crises (BASIC) Research programme aims to inform policy and programming on effective social assistance in situations of crisis, including those experiencing climate-related shocks and stressors, protracted conflict and forced displacement.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Social Protection PEA; conflict / conflito; social protection / proteção social

Mozambique: ExxonMobil again postpones final decision on Rovuma LNG (Mozambique, 2021)
US oil company Exxon has postponed for the third consecutive year the Final Investment Decision on the natural gas exploration project in Mozambique, putting the $30 billion investment in doubt. According to Bloomberg news agency, which quotes the company's Senior Vice President Neil Chapman, Nei
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; private sector / setor privado

Regional Integration at the Forefront of Mozambique’s Energy Success - Hundermark, Charnè (cnbcafrica, 2021)
As one of leading resource-rich countries in sub-Saharan Africa, Mozambique has the potential to not only significantly advance its own socioeconomic status, but also dramatically boost economic growth throughout the region. According to the World Bank Group, regional integration helps countries to overcome divisions that impede the flow of goods, services, capital, people and ideas. As large-scale energy projects are expected to come online in Mozambique through 2023, the country has observed renewed political commitment to establishing sustainable regional integration with neighboring governments and private operators.
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; L - english / inglês; economic development / desenvolvimento económico

Signing of Grant Agreement with Mozambique: Contributing to the improvement of people’s living environment in Niassa Province through the construction of a rural water supply facility - JICA (2021)
On February 26, 2021, the Japan International Cooperation Agency (JICA) signed a grant agreement with the Government of the Republic of Mozambique in Maputo, to provide grant aid of up to 2.076billion yen for the Project for the Construction of a Rural Water Supply Facility in Niassa Province. Under this project, people’s living environment in Niassa Province will improve through installing a rural water supply facility, which will allow access to safe and clean water. It is expected that this project will lead to reduction of waterborne diseases and nutritional improvement. Measures to combat climate change will also be conducted, and this project will contribute to the achievement of SDGs Goals 3, 6, and 13.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; access to services / acesso a serviços; climate change / mudanças climáticas; infrastructure / infrastrutura

Mozambique: Civilians killed as war crimes committed by armed group, government forces, and private military contractors – new report (2021)
The new report documents serious violations of international humanitarian law by all parties to the conflict in Cabo Delgado.
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Mozambique: How Total plans to protects its $15bn major gas project - Le Bec, Christophe (The Africa Report.com, 2021)
Total is going ahead with its Mozambique LNG project despite a major armed insurgency in Cabo Delgado. This article discusses plans to secure its Afungi facility, including security forces involved. Facility employment is projected to triple by 2022, from 5,000 in 2020 to 15,000 by 2022.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; employment / emprego; extractive industries / indústrias extractivas; private sector / setor privado

Jovens moçambicanos descontentes com falta de oportunidades (DW.COM, 2020)
No Dia Mundial da Juventude, jovens da província moçambicana de Nampula queixam-se da falta de emprego, de habitação e de acesso ao crédito financeiro. O novo coronavírus também é um dos maiores problemas atualmente.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - portuguese / português; employment / emprego; youth / juventude

Covid-19: Organizações questionam gastos do Governo moçambicano | DW | 11.08.2020 - Deutsche Welle (DW.COM, 2020)
Em Moçambique, a sociedade civil aponta falta de transparência e pede esclarecimentos ao Governo sobre os 14 mil contratos sem concurso público e os 68 mil milhões de meticais gastos durante o estado de emergência.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; accountability / responsabilização; health - COVID-19 / saúde – COVID-19; health / saúde; transparency / transparência

Niassa: MASC desencoraja envolvimento de jovens nos ataques terroristas - User, Super (2020)
A Fundação MASC - Mecanismo de Apoio a Sociedade Civil, no Niassa, desencoraja o envolvimento de jovens nos ataques terroristas na vizinha província d...
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - portuguese / português; civil society / sociedade civil; conflict / conflito; youth / juventude

The Secret to the Northern Mozambique Insurgency’s Success - Emilia Columbo (War on the Rocks, 2020)
This has been a banner year for Ahlu-Sunnah Wa-Jama (ASWJ) — or al-Shabaab, as locals call it — operating in northern Mozambique. Between January and
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Mozambique LNG Project Could Be Transformational For Mozambique — If Western Environmentalists Don’t Interfere | Africa Oil & Power (2020)
NJ Ayuk discusses the Mozambique LNG project.
Section: Interviews
Keywords: #Reporting & Media / Reportagem & Mídia; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; extractive industries / indústrias extractivas; private sector / setor privado

Insurgência: No lançamento da ADIN Nyusi ameaça reagir em caso de atentado a coesão - Anacleto, Delfim (Deutsche Welle (DW), 2020)
O norte de Moçambique passa a partir de hoje a contar com uma Agência de Desenvolvimento integrado para promover o crescimento económico e social. E em Pemba, Filipe Nyusi falou com o bispo de Pemba sobre a insurgência.
Keywords: *indexed; ADIN (Agency for Integrated Development of the North); G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA

Narrativas Alternativas: Lançamento Do Álbum Moçambique Yethu! #stopviolenciaextremista - MASC, Fundação (Fundação MASC, 2020)
Desde o final de 2017, Cabo Delgado, tem sido palco de violentos ataques de grupos […]
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; civil society / sociedade civil; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; youth / juventude

Tanzaniano recruta jovens no Niassa para ataques em Cabo Delgado - Governo de Moçambique (Governo de Moçambique, 2019)
Alguns jovens do distrito de Mecula, no Niassa, norte de Moçambique, são recrutados para integrarem o grupo de malfeitores que protagonizam ataques armados nos distritos do norte da vizinha província de Cabo Delgado.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; GP - Niassa; L - portuguese / português; youth / juventude

Cyclones Idai and Kenneth - OCHA (United Nations Office for the Coordination of Humanitarian Affairs, 2019)
In March and April 2019, Southern Africa was hit by two subsequent cyclones that left a trail of destruction in their path, and close to 2.2 million people in need urgent assistance in Mozambique alone. On the night of 14 to 15 March Tropical Cyclone Idai made landfall near Beira City, Sofala Province, in central Mozambique. The cyclone brought torrential rains and winds to Sofala, Zambezia, Manica and Inhambane provinces. Cyclone Idai continued across land as a Tropical Storm and hit eastern Zimbabwe with heavy rains and strong winds. The storm caused high winds and heavy precipitation in Chimanimani and Chipinge districts causing riverine and flash flooding and subsequent deaths, destruction of livelihoods and properties. Idai left more than 600 people dead and an estimated 1.85 million people in need in Mozambique alone. On 24 April, Tropical Cyclone Kenneth passed north of the Comoros Islands, hitting the northern island of Ngazidja. On the evening of 25 April, the cyclone made landfall in Mozambique between the districts of Macomia and Mocimboa da Praia in Cabo Delgado province. With wind gusts of up to 220km/h, Tropical Cyclone Kenneth became the strongest cyclone to ever hit the African continent. Cyclone Kenneth left 374,000 people in need. Tropical Cyclone Kenneth reportedly caused three deaths, at least 20 injuries and extensive damage to houses across the archipelago. Preliminary estimates indicate that at least 1,000 people were displaced, most of them children. While assessments are ongoing, initial reports from the Comoros indicate that several villages were flooded due to sea surges and broken dykes, and that power was cut in multiple locations. Roads have reportedly been damaged and cut off by fallen trees, while telephone poles are down in multiple locations. Latest updates on the response can be found here. It is the first time in recorded history that two strong tropical cyclones have hit Mozambique in the same season. Cyclone Idai As of 9 April, the official death toll caused by Cyclone Idai stands at 602 people, with more than 1,600 people injured, according to the Government. Many people are displaced, and communicable diseases are on the rise. Of particular concern are cholera and malaria. An oral vaccination campaign reached over 800,000 people by early April 2018. Many schools are damaged or used as shelter for displaced people. Humanitarian partners continue to call for any relocations out of schools or elsewhere to be safe, dignified and voluntary. In figures People in need 1.85M People targeted 1.72M Funding needed $282M Cyclone Kenneth The cyclone hit Mozambique more north than Cyclone Idai, with Quissanga, Macomia, and Ibo districts in Cabo Delgado hardest-hit, according to preliminary government reports. At least 45 deaths have been reported and 18,029 people were initially reportedly displaced, according to the National Disaster Management Institute (INGC). Cyclone Kenneth made landfall at the end of the rainy season, when river levels were already high, increasing the risk of river flooding. Humanitarian needs in Mozambique have sky-rocketed, and the humanitarian response will need to rapidly scale-up while capacity and funding are limited. In figures People in need 374K People targeted 374K Funding needed $104M On 16 March, Cyclone Idai hit eastern Zimbabwe with heavy rains and strong winds. The storm caused high winds and heavy precipitation in Chimanimani and Chipinge districts causing riverine and flash flooding and subsequent deaths, destruction of livelihoods and properties. The homes of at least 4,000 households are destroyed or currently uninhabitable. The seven districts affected by Cyclone Idai- Chipinge, Chimanimani, Buhera, Bikita, Mutare, Gutu, and Chiredzi - multisectoral support will be required to speed recovery. The livelihoods of over 270,000 people across these districts has been affected. Those lviing in Chipinge and Chimanimani districts are worst hit. In early March, heavy rains and flooding linked to Cyclone Idai killed 60 people, displaced nearly 87,000 people and affected nearly 870,000 persons. The Government of Malawi declared a ‘state of disaster’ on 8 March and subsequently launched a Flood Response Plan and Appeal on 28 March to support life-saving humanitarian interventions in 15 affected districts. Humanitarian partners and the Government of Malawi have reached over 400,000 persons with immediate life-saving relief support which includes food, medicine, shelter, protection services and other non-food-items such as water, sanitation and hygiene supplies. A Post Disaster Needs Assessment (PDNA) has been undertaken by the Malawi Government, UN, World Bank and European Union to assess damages, losses and priority recovery needs and costs. The data and information collected will inform the Government’s recovery plan.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; climate change / mudanças climáticas; natural disasters / desastres naturais

When a health system turns into a Tower of Babel: Mozambique's experience - Namburete, Denise (Institute of Development Studies, 2018)
Likened to the Tower of Babel legend, the Mozambican national health system speaks several languages and pursues a range of different interests, answering to a number of partners and other bilateral and multilateral actors who all have some kind of circumstantial and contextual interest. When the Paris Declaration on Aid Effectiveness was endorsed, Mozambique may […]
Keywords: G - Mozambique / Moçambique; L - english / inglês; health / saúde

Mozambique’s insurgency: a new Boko Haram or youth demanding an end to marginalisation? - Hanlon, Joseph (Africa at LSE, 2018)
Joseph Hanlon argues that Mozambique’s new “Islamic” insurgency is about marginalised youth demanding to be heard, and therefore is similar to anti-establishment protest across the world.
Keywords: *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

New Action Plan for Health Promotion in Cabo Delgado (Mozambique) (2018)
In Cabo Delgado - Mozambique, we are giving support to the Provincial Health Directorate (DPS-CD) in developing an essential tool for the promotion of health in the Province: The Action Plan for Health Promotion.
Keywords: *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; health / saúde

Falta de alimentos agrava-se em zonas atacadas na província de Cabo Delgado - Macuácua, Amandio Roberto (Jornal Notícias, 2018)
A falta de alimentos está a agravar-se em zonas do interior na província de Cabo Delgado por causa dos ataques causados por grupos armados que têm levado a população a abandonar terras, alerta um relatório ontem divulgado.
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict / conflito

No Niassa, jovens consomem cada vez mais álcool de forma excessiva - Deutsche Welle (DW.COM, 2017)
Na província do norte de Moçambique, muitos adolescentes e jovens entregam-se ao vício por falta de ocupação profissional.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - portuguese / português; employment / emprego; youth / juventude

Relatório de Pesquisa Formativa – Educação e Saúde de Qualidade (2014) (Responsabilização Social em Moçambique, 2016)
As intervenções programadas pelo CEP enquadram-se num contexto em que Moçambique regista um progressivo aumento na disponibilidade de serviços de educação e saúde, ao mesmo tempo em que enfr…
Keywords: G - Mozambique / Moçambique; L - portuguese / português

Estrutura Geológica de Moçambique - Nogar Boca (2016)
Tema: Estrutura Geológica de Moçambique A estrutura geológica de Moçambique é resultado da interacção de vários processos, sobretudo os endógenos (internos) e exógenos (externos), que se fizeram sentir e ainda sentem-se na actual região da África Austral, onde Moçambique faz parte. Do ponto de vista geológico, Moçambique apresenta duas grandes unidades geológicas: Pré-câmbrico Fanerozóico
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; natural resources / recursos naturais

The land grabbers of the Nacala Corridor - UNAC (GRAIN, 2015)
A new report by Mozambique's National Farmers' Union (UNAC) and GRAIN shows there is a colonial-style scramble for Africa's farm lands under way. Politically-connected companies based in offshore tax havens have grabbed hundreds of thousands of hectares of farmland from peasants in Mozambique.
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; Important; L - english / inglês; Northern PEA; law / direito

Crónicas dos Motins - Granjo, Paulo (Anropocoiso - Blog de Paulo Granjo, 2008)
Mensagens correspondentes à consulta "Crónicas dos Motins".
Keywords: *non-public; G - Mozambique / Moçambique; L - portuguese / português; conflict / conflito

All hands on deck: Harnessing accountability through external public audits | Publications (International Budget Partnership)
This report is the first ever comprehensive look at the strength of audit and oversight systems globally and comes at a time when supreme audit institutions (SAIs) are under enormous pressure to ensure governments are effective stewards of COVID-19 emergency spending in ways that advance the public interest and protect development progress.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização

Clean Mining Gains Foothold In Mozambique | Africa Oil & Power
The mining sector in Mozambique is in the midst of transformation, as it realigns with the clean energy transition.
Section: News & Articles
Keywords: G - Mozambique / Moçambique; L - english / inglês

Mozambique LNG Project, Cabo Delgado, Mozambique
The Area 1 Mozambique LNG project comprises the offshore Golfinho-Atum gas field development and a 12.88Mtpa onshore LNG facility in Mozambique.
Keywords: FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; extractive industries / indústrias extractivas

Development for Whom?: From the Case of the ProSAVANA Project in Mozambique – Master of Development Practice - Go Suzui
ProSAVANA project in Mozambique There are tremendous numbers of development projects all over the world. Mozambique is one of the least developed countries. A serious issue in Mozambique is food security. Even though 80 percent of the labor force in Mozambique engages in agriculture (USAID 2017), Mozambique’s farmland is tropical savanna that features very poor soil quality, and Mozambique does not have technologies to overcome this issue. As related to a food security issue, more than two out of five children under five years old are malnourished in Mozambique (UNICEF Mozambique 2017). The government of Mozambique decided to transform the current agriculture system and ensure food security. ProSAVANA is a triangular cooperation program among Mozambique, Brazil and Japan since 2009. The Japan International Cooperation Agency, the Japanese Ministry of Foreign Affairs and the Brazilian Cooperation Agency have participated in this project. The main purpose is to “improve the livelihood of inhabitants of the Nacala Corridor through inclusive and sustainable agricultural and regional development” and to “create employment through agricultural investment and establishment of a supply chain,” (ProSAVANA 2016). It seems that ProSAVANA has positive impacts on agriculture and on the total GDP of Mozambique and can improve childhood nutrition.
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; government policy / politica governamental

COVID-19 in Mozambique | DIIS - Helene Maria Kyed
police violence, mistrust of government and the fear of hunger
Keywords: G - Mozambique / Moçambique; L - english / inglês

Deviations between the Planned and the Execution Undermine the Health Budget – Observatório do Cidadão para Saúde - Observatório Cidadão para Saúde
In Mozambique, health services are mostly provided by the public sector, and it is the responsibility of the Ministry of Health (MISAU) to enable the creation, planning and control of national health policies. The health sector is the third sector that absorbs most resources from the State Budget (OE), followed by the Education and Infrastructure sectors, according to the methodology presented in the budget documents related to the economic and social sectors. This sector is divided into three levels: namely, the Central Level, which is represented by MISAU; The Provincial Level, which is represented by the Provincial Health Directorates (DPS); and Finally, we have the District Level, which is represented by the Health, Women and Social Action Secretariats (SDSMAS). Therefore, it will be based on these levels that our analysis of allocations to the health sector in the period from 2015 to 2020 will be undertaken.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; budget / orçamento; health - health services / serviços de saúde